2022
DOI: 10.1186/s13756-022-01078-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of surgical site infections and related antibiotic resistance in Freetown, Sierra Leone: a prospective cohort study

Abstract: Background There is limited information on surgical site infections (SSI) and the related antibiotic resistance needed to guide their management and prevention in Sierra Leone. In this study, we aimed to establish the incidence and risk factors of SSI and the related antibiotic resistance among adults attending a tertiary hospital, and a secondary health facility in Freetown, Sierra Leone. Methods This is a prospective cohort study designed to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
4
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 23 publications
4
35
4
6
Order By: Relevance
“…Some of these challenges include a high burden of extended-spectrum β-lactase (ESBL)-producing gram-negative bacteria and gaps in hand hygiene implementation. [10][11][12][13] The abuse and overuse of antibiotics, including surgical antibiotic prophylaxis, is one of the main reasons for the increased burden of AMR. 14,15 The use of antibiotics is essential to preventing surgicalsite infections.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these challenges include a high burden of extended-spectrum β-lactase (ESBL)-producing gram-negative bacteria and gaps in hand hygiene implementation. [10][11][12][13] The abuse and overuse of antibiotics, including surgical antibiotic prophylaxis, is one of the main reasons for the increased burden of AMR. 14,15 The use of antibiotics is essential to preventing surgicalsite infections.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the procedure and patient's underlying condition, the frequency of surgical site infections ranges from 0.5 percent to 15 percent [8]. The key clinical components of the definition include purulent discharge around the lesion, pus at the drain insertion site, and cellulitis that is spreading from the wound [9].…”
Section: Surgical Site Infectionsmentioning
confidence: 99%
“…Complicating the issue is the high incidence of multidrug resistant pathogens in patients with HAIs. Studies conducted in Sierra Leone reported high prevalence rates of extended-spectrum beta-lactamase-producing Gram negative bacteria in patients with healthcare-associated infections [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%